Effects of a Lidocaine-Loaded Poloxamer/Alginate/CaCl2 Mixture on Postoperative Pain and Adhesion in a Rat Model of Incisional Pain. (July 2017) - Choi, Geun Joo; Kang, Hyun; Hong, Min Eui; Shin, Hwa Yong; Baek, Chong Wha; Jung, Yong Hun; Lee, Younsuk; Kim, Jeong Wook; Park, IL Kyu; Cho, Wan Jin
Abstract : BACKGROUND: Pain and adhesion are problematic issues after surgery. Lidocaine has analgesics and anti-inflammatory properties, and poloxamer/alginate/CaCl2 (PACM) is a known antiadhesive agent. We hypothesized that the novel combination of lidocaine as chemical barrier and PACM as physical barrier would be beneficial for both postoperative pain and adhesion. The purpose of this study was to investigate the effects of lidocaine-loaded PACM in a rat model of incisional pain. Primary outcome was to evaluate between-group differences for the mechanical withdrawal threshold (MWT) measured by von Frey filament in various concentrations of lidocaine-loaded PACM applied, PACM applied, and sham-operated groups. METHODS: Male Sprague-Dawley rats were used for the postoperative pain model. After plantar incision and adhesion formation, 0.5%, 1%, 2%, and 4% lidocaine-loaded PACM, PACM only, nothing, and 4% lidocaine only were applied at the incision site in groups PL0.5, PL1, PL2, PL4, P, S, and L4, respectively. MWT using a von Frey filament and serum levels of tumor necrosis factor-α, interleukin (IL)-1β, IL-6, and high-sensitivity C-reactive protein were measured. Rats were euthanized 2 weeks after surgery, and inflammation and fibrosis were assessed with microscopy. Data were analyzed using the Kruskal–Wallis test, multivariate analysis of variance, and linear mixed-effect model. To compare MWT at each time point, analysis of variance with Bonferroni correction was used. RESULTS: Multivariate analysis of variance showed that 4% lidocaine-loaded PACM significantly raised the MWT up to 6 and 8 hours after surgery compared with lidocaine-unloaded groups S and P, respectively; 2% lidocaine-loaded PACM significantly increased the MWT at 4 hours after surgery compared with groups S and C. Linear mixed-effect model showed that the MWT (estimated difference in means [95% confidence interval]) was significantly increased in groups PL2 and PL4 (6.58 [2.52–10.63], P = .002; 11.46 [7.40–15.51], P < .001, respectively) compared with group P. Inflammation and fibrosis seen on microscopic evaluation were significantly decreased in groups PL2 and PL4 compared with group S. Four percent of lidocaine only showed a significant reduction in inflammation. Serum levels of tumor necrosis factor-α, IL-1β, IL-6, and high-sensitivity C-reactive protein were decreased in lidocaine-loaded groups compared with group S or P at 1, 2, and 48 hours, and 2 weeks after surgery, respectively. CONCLUSIONS: Lidocaine-loaded PACM reduced postoperative pain, and lidocaine strengthened the antiadhesive effect of PACM. Abstract : Published ahead of print March 17, 2017.